Ensino remoto e formação da(o) psicóloga(o), sob a perspectiva Histórico-Cultural - Brimáuria Nascimento da Luz (2023)
Research with coordinators, professors and university students denounce the countless, immense and intense challenges faced in Higher Education and that the pandemic context of Covid-19, an infectious disease caused by the SARS-Cov-2 virus, in Brazil, helped to reveal and accentuate. This pandemic led to the implementation of Emergency Remote Teaching - ERT. We understand that Remote Learning (RL) has also caused impacts on the academic, social and historical background of university students in general. Considering this aspect, our general objective is to identify and analyze the effects of remote teaching for the training of psychologists in some Higher Education institutions in the State of Goiás, based on theoretical assumptions of historical-cultural psychology. We also intend to discuss some aspects directly related to School and Educational Psychology, obtained in the questionnaires, in particular regarding Law 13.935/2019, which provides for the insertion of Psychology and Social Assistance in Basic Education. The study is based on Historical-Cultural Psychology. As a methodology we will use bibliographical and empirical research. The dissertation is composed of three sections. The first contextualizes the psychologists’ training in Brazil, presenting the legislation about the functioning of remote teaching and addressing some aspects of the performance and training of school psychologists. In section 2, we address the relation between development and learning from the perspective of Historical-Cultural Psychology. In section 3, we present the results of the empirical research, which was composed of questionnaires answered by eight coordinators/teachers and 41 students. As a result, we found that most teachers, as well as students, consider that the teaching-learning process was impacted by the Covid-19 pandemic and remote teaching. Research participants report difficulties in the teacher-student and student-student relationship due to distancing. Even in the face of the difficulties imposed by the ERE, 87.5% of teachers and 58.5% of undergraduates considered that teaching was effective in this modality. We also found that all teachers and 82.9% of students declared to have knowledge about the aforementioned Law 13.935/2019 and that training and performance is directed, almost entirely, towards a critical conception of School and Educational Psychology. In view of this, we understand that the Historical-cultural perspective can reveal the direct and indirect countless implications in the education area, in particular, Higher Education, in the pandemic context, bringing undeniable contributions to facing the different types of challenges and impacts for the individual: social and historical human. It remains for us now, in the psychologists’ training, to rescue the knowledge that has not been appropriated by the students, so that the university fulfills its function of human formation and professional preparation.